2005
DOI: 10.2337/diabetes.54.5.1523
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Binding Lectin as a Predictor of Microalbuminuria in Type 1 Diabetes

Abstract: A substantial portion of type 1 diabetic patients develop diabetic nephropathy, whereas others seem to be protected from this complication. Persistent microalbuminuria (urinary albumin excretion rate [UAER] of 30 -300 mg/24 h) is an established risk factor for the development of overt diabetic nephropathy, characterized by albuminuria Ͼ300 mg/24 h (1). Microalbuminuria may be regarded as an early marker of diabetic kidney disease, as early renal structural lesions can be detected at this stage (2). Genetic sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 33 publications
4
83
0
Order By: Relevance
“…These observations seem to contradict recent articles describing increased MBL concentrations in patients with type 1 diabetes with microvascular complications [29][30][31][32][33]. However, MBL plays a dual role in modifying inflammatory responses to injury [34].…”
Section: Discussionmentioning
confidence: 70%
“…These observations seem to contradict recent articles describing increased MBL concentrations in patients with type 1 diabetes with microvascular complications [29][30][31][32][33]. However, MBL plays a dual role in modifying inflammatory responses to injury [34].…”
Section: Discussionmentioning
confidence: 70%
“…Diabetic nephropathy was more prevalent among type 1 diabetic patients with a high MBL expression genotype and high circulating MBL levels than among patients with a low MBL genotype and low serum MBL levels [5]. In a recent study in type 1 diabetic patients, followed for 18 years from diagnosis, high MBL level at baseline was a significant predictor of the development of either microalbuminuria or overt nephropathy [7].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, in a cohort study of type 1 diabetic patients followed for 18 years from diagnosis, serum MBL was a significant predictor of later renal impairment. In patients with MBL levels above the median, 41% developed micro-or macroalbuminuria, in contrast to 26% of patients with levels below the median [7]. To evaluate a potential specific effect of MBL on the pathogenesis of diabetic kidney disease, we induced type 1 diabetes in wild-type and genetically modified MBL double knockout mice and examined the functional and structural renal changes.…”
mentioning
confidence: 99%
“…Several studies have demonstrated the close association between the lectin pathway of complement activation and diabetic nephropathy. In particular, high concentrations of the carbohydrate pattern-recognition molecule mannan-binding lectin (MBL), which initiates complement activation, are linked to diabetic nephropathy defined by urinary albumin excretion rate (2)(3)(4)(5)(6)(7)(8). In the present cohort, we previously showed the cross-sectional association between MBL2 genotype and diabetic nephropathy (2).…”
mentioning
confidence: 90%